EFEKTIVITAS PEMBERLAKUAN SURAT IZIN MENGEMUDI TERHADAP PENGEMUDI DIBAWAH UMUR KECAMATAN KALIDERES, JAKARTA BARAT - Gladys Natalie Aurielle Sirait; Gunawan Djajaputra (Fakultas Hukum Universitas Tarumanagara, 2021)
The requirements for motorcycle drivers are regulated in Law No. 22 of 2009 concerning Road Traffic and Transportation, namely in Article 80 which reads